2022
DOI: 10.1111/opn.12519
|View full text |Cite
|
Sign up to set email alerts
|

Professional development and career planning for nurses working in care homes for older people: A scoping review

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…There is some evidence to show the positive impact of appraisals on quality of care provided by support workers, but it is less clear whether appraisals or mentorship support career development or progression ( 183 , 184 ). There is evidence internationally to show that having opportunities for training, CPD and a supportive work environment, supports employees in their career goals and commitment to stay in home care work ( 133 , 171 , 172 , 185 187 ). What is clear is that some provider organisations take a more active approach to career progression than others, emphasising the importance of crafted career pathways for staff advancement and retention of employees and their skills within the organisation ( 188 ).…”
Section: Resultsmentioning
confidence: 99%
“…There is some evidence to show the positive impact of appraisals on quality of care provided by support workers, but it is less clear whether appraisals or mentorship support career development or progression ( 183 , 184 ). There is evidence internationally to show that having opportunities for training, CPD and a supportive work environment, supports employees in their career goals and commitment to stay in home care work ( 133 , 171 , 172 , 185 187 ). What is clear is that some provider organisations take a more active approach to career progression than others, emphasising the importance of crafted career pathways for staff advancement and retention of employees and their skills within the organisation ( 188 ).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, nurses with more work experience want clear criteria for professional roles and a clear career path [32]. A review of other studies found that the key factors that supported professional development and career planning were access to structured learning opportunities in a supportive work environment, flexible working hours, and integration of leadership development [33].…”
Section: Discussionmentioning
confidence: 99%
“…Nurses' organizations need to carry out strategic work on the career information and resources that are crucial. Individuals experience remarkable time and fnancial pressures during education ( [22]). Employers who provide support to overcome these challenges need to implement multifaceted strategic planning and collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reviews on career development in nursing have covered nurses' career intentions [8,14], professional development [22,23], career success [15], career path options [12], and the implementation of clinical ladder programs [21]. Instead, knowledge on organizational support for nurses' CP&D has been fragmented and needs to be brought together to provide the basis for the evidence-based development of nurses' working lives.…”
Section: Introductionmentioning
confidence: 99%